Neuropsychophysiological Effects of a Single Functional Neurology Intervention on Semicircular Canals Stimuli Dysfunction - Escribano-Colmena, Guillermo; Rey-Mota, Jorge; Clemente-Suárez, Vicente Javier (Behavioral sciences, 2025)
This exploratory observational study analyzed the neuropsychophysiological effects of Functional Neurology interventions on semicircular canal dysfunction, with a focus on enhancing neuromuscular responses and pain perception. A cohort of 45 healthy volunteers, comprising both males and females with an average age of 26.5 years, participated in this controlled, experimental study. The methodology involved baseline assessments of their psychophysiological state and physical abilities, followed by specific tests to analyze semicircular canal dysfunction. Participants then received customized Functional Neurology treatment aimed at correcting detected neuromuscular imbalances. The effects of Functional Neurology treatment were evaluated comparing variables such as hand strength, blood oxygen saturation, heart rate, and the Critical Flicker Fusion Threshold before and after the intervention. The study found a significant increase in the tolerance to semicircular canal stimuli, from an average of 1.0 ± 0.0 stimuli tolerated before intervention to 21.0 ± 14.0 post-treatment, suggesting that Functional Neurology can markedly improve neuromuscular responses in the context of vestibular dysfunction. However, no significant changes were observed in blood oxygen saturation or cortical arousal, indicating that these specific interventions may not affect all psychophysiological parameters. In conclusion, Functional Neurology interventions show promise in treating vestibular disorders by significantly enhancing neuromuscular response and pain tolerance, despite not impacting other psychophysiological measures. This research underscores the potential of Functional Neurology in improving the quality of life for individuals with vestibular dysfunctions and advocates for further exploration into its comprehensive neurophysiological effects.